2019
DOI: 10.1002/cpsc.98
|View full text |Cite
|
Sign up to set email alerts
|

Top‐Down Inhibition (TDi) and Baseline Activation (BLa): Controlling Signal Transduction When Endogenous Cytokines are Ruining Your Differentiation

Abstract: In the 20 years since the first human pluripotent stem cell (hPSC) lines were established, there have been a plethora of protocols developed that allow us to generate a wide range of human cell types in vitro. Efforts to achieve a greater degree of specificity and efficiency in generating desired cell types have resulted in increasingly complex approaches. The magnitude and timing of signals has become key, and the concept of a “fully defined” system is a forever sought‐after goal with shifting goalposts. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This hypothesis was further addressed by Hackland and colleagues, who suggested that variations in endogenous BMP ligand production levels across hPSC lines and culture systems account for these variable and partly contradictory results [ 140 ]. They proposed mediating a controlled activation of BMP signaling by combining a saturating concentration of exogenous BMP4 with simultaneous addition of a BMP antagonist, DMH1, in a defined, sub-maximal concentration, to precisely tune an optimal BMP activity, in a top-down manner [ 140 , 141 ]. With this method, consistent results of robust neural crest induction across different hPSC lines were achieved.…”
Section: In Vitro Differentiation Of Schwann Cellsmentioning
confidence: 99%
“…This hypothesis was further addressed by Hackland and colleagues, who suggested that variations in endogenous BMP ligand production levels across hPSC lines and culture systems account for these variable and partly contradictory results [ 140 ]. They proposed mediating a controlled activation of BMP signaling by combining a saturating concentration of exogenous BMP4 with simultaneous addition of a BMP antagonist, DMH1, in a defined, sub-maximal concentration, to precisely tune an optimal BMP activity, in a top-down manner [ 140 , 141 ]. With this method, consistent results of robust neural crest induction across different hPSC lines were achieved.…”
Section: In Vitro Differentiation Of Schwann Cellsmentioning
confidence: 99%
“…Furthermore, high BMP signalling can lead to specification of the cranial placode or non-neural ectoderm whereas low BMP can result in neuroectoderm specification [ 78 ]. As a result, more recent improved protocols which modulate BMP levels through top-down inhibition demonstrated that a precise level of intermediate BMP activity is required to specify NC efficiently and reproducibly from hPSCs in vitro [ 79 , 80 ]. A common feature of these approaches is that the NC cells they give rise to exhibit minimal HOX gene expression indicating a cranial axial identity.…”
Section: Development In Vitro : Generating Nc Cell...mentioning
confidence: 99%